A New Method of Kronecker Product Decomposition - Yi Wu (Journal of Mathematics)
Kronecker product decomposition is often applied in various fields such as particle physics, signal processing, image processing, semidefinite programming, quantum computing, and matrix time series analysis. In the paper, a new method of Kronecker product decomposition is proposed. Theoretical results ensure that the new method is convergent and stable. The simulation results show that the new method is far faster than the known method. In fact, the new method is very applicable for exact decomposition, fast decomposition, big matrix decomposition, and online decomposition of Kronecker products. At last, the extension direction of the new method is discussed.